ANALISIS PERAN KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONALISME GURU DI MI TERPADU AL MABRUR TAWANGSARI SUKOHARJO TAHUN 2022/2023 - Habibati, Aida; Amin, Lailla Hidayatul; Rochmawan, Alfian Eko (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This research begins by analyzing the competence and professionalism of dozens of teaching staff, before looking at the role of school principals in optimizing them. This research aims to explain teacher professionalism at MI Integrated Al Mabrur Tawangsari Sukoharjo, and to determine the role of the principal in optimizing teacher professionalism at MI Integrated Al Mabrur Tawangsari Sukoharjo. In research on the role of school principals in optimizing teacher professionalism at Al-Mabrur Tawangsari Integrated Madrasah Ibtidaiyah (MI), Sukoharjo, a qualitative descriptive method was used. Research subjects were determined and selected using purposive techniques. Data collection techniques used were observation, interviews, literature study and documentation. The data analysis technique was carried out by using qualitative data analysis using an inductive model. Based on the results of research on the role of school principals in increasing teacher professionalism at Al Mabrur Tawangsari Integrated MI, it shows that the achievement of the teacher professionalism optimization program must be fully supported starting from initiation and participation. Programs that have been implemented such as comparative studies, seminars, training, education and monitoring must be carried out on an ongoing basis.